The Potential Benefits of Applying Recent Advances in Esophageal Motility Testing in Patients with Esophageal Atresia - Rommel, Nathalie; Rayyan, Maissa; Scheerens, Charlotte; Omari, Taher (Frontiers in Pediatrics, 2017)
Infants and children with oesophageal atresia commonly present with swallowing dysfunction or dysphagia. Dysphagia can lead to a range of significant consequences such as aspiration pneumonia, malnutrition, dehydration and food impaction. To improve oral intake, the clinical diagnosis of dysphagia in patients with esophageal atresia should focus on both the pharynx and the esophagus. To characterize the complex interactions of bolus flow and motor function between mouth, pharynx and esophagus, a detailed understanding of normal and abnormal deglutition is required through the use of adequate and objective assessment techniques. As clinical symptoms do not correlate well with conventional assessment methods of motor function such as radiology or manometry but do correlate with bolus flow, the current state of the art diagnosis involves high-resolution manometry combined with impedance measurements to characterize the interplay between esophageal motor function and bolus clearance. Using a novel pressure flow analysis (PFA) method as an integrated analysis method of manometric and impedance measurements, differentiation of patients with impaired EGJ relaxation from patients with bolus outflow disorders is clinically relevant. In this, pressure flow matrix categorizing the quantitative PFA measures may be used to make rational therapeutic decisions in patients with esophageal atresia. Through more advanced diagnostics, improved understanding of pathophysiology may improve our patient care by directly targeting the failed biomechanics of both the pharynx and the esophagus.